A Rare Complication of Anomalous Left Coronary Artery From the Pulmonary Artery Identified by Point-of-Care Ultrasound. Issue 3 (29th March 2023) - Gutowski, Joseph N.; Donovan, Denis J.; Firnberg, Maytal T.; Constantinescu, Andrei; Kennedy, Thomas M.
Abstract: Point-of-care ultrasound is a valuable tool in the evaluation of undifferentiated respiratory distress in children. This case report describes a 9-month-old male infant who presented with 4 months of progressively worsening cough and was found to be tachypneic in the emergency department. Chest radiography revealed complete opacification of the left hemithorax with cardiomegaly. Point-of-care ultrasound demonstrated atelectasis of the entire left lung and severe dilation of the left ventricle with poor function. Electrocardiogram and echocardiogram findings were consistent with a diagnosis of anomalous left coronary artery from the pulmonary artery. The patient underwent successful cardiac surgery to improve myocardial perfusion. Bronchoscopy visualized the etiology of his atelectasis, pulsatile compression of the left mainstem bronchus by the dilated heart. Focused cardiac and lung ultrasound techniques, as well as pertinent sonographic findings, are reviewed.